Managerial Assessment of Organizational Components - Wahba, Mahmoud A.; Shapiro, Harris J. (Academy of Management Journal, 1973)
The need for the development of criterion measures of organizational components? effectiveness is discussed. Managers at different organizational levels ranked twenty possible criterion measures according to their importance. The results showed that the managerial model of component effectiveness is based on three dimensions: the performance dimension, the intercomponent dimension, and the intracomponent dimension.